Analisis Kelayakan Usahatani Kelapa Dalam Migran Jawa Di Lahan Pasang Surut Provinsi Sumatera Selatan - Yudhi Zuriah Wirya Purba (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Purba et al, 2016. Feasibility Analysis of Coconut Farming Java Migran in Tidal Land District of South Sumatra Province. JLSO 5(1):95-104.This study aims to calculate the production cost incurred, income received from coconut farming and analyze the feasibility of coconut farming by Javanesse migrants on tidal land of the Sungai Semut village, District of Makarti Jaya, Banyuasin Regency. The research methods being conducted is survey and the sampling method is simple random sampling, and the number of samples taken are 15 farmers from entire 160 of the population. The results shown that the average production cost number spent in coconut farming is Rp 3.687.512,00, meanwhile the average income earned is Rp 11.282.488,00 for each production process. Financially, the results of analysis shown that with the NPV atRp 14.378.857,00 hence the value of IRR is 22,98 percents and the value of Net B/C 1,65 that means the coconut farming is feasible to be implemented.